PENGARUH INTENSITAS TERPAAN KAMPANYE ANTI-ROKOK DI AKUN INSTAGRAM @koalisibebas_tar DAN TINGKAT KONFORMITAS TERHADAP TEMAN SEBAYA TERHADAP KEPUTUSAN BERHENTI MEROKOK MAHASISWA - Edel Martoma Pardede; Sunarto Sunarto (Interaksi Online, 2026)
The high prevalence of smoking among young people in Indonesia, particularly university students, remains a serious public health concern. This study examines the influence of the intensity of anti-smoking campaign exposure on the Instagram account @koalisibebas_tar and the level of peer conformity on university students' decision to quit smoking. The theoretical framework used is the Elaboration Likelihood Model (ELM) developed by Petty and Cacioppo (1986), which explains that attitude change occurs through two persuasion routes: the central route (deep message processing) and the peripheral route (superficial processing based on external cues). This study employs a quantitative explanatory approach using a survey method. Data were collected through questionnaires distributed to 100 respondents who are students of FISIP Universitas Diponegoro and have consumed content from the @koalisibebas_tar Instagram account. Data were analyzed using hierarchical multiple linear regression. The results show that anti-smoking campaign exposure (X) significantly influences the decision to quit smoking (Y) with a correlation coefficient of R = 0.581 (sig. 0.000). When mediated by peer conformity, the correlation increases to R = 0.640 (sig. 0.002), demonstrating that peer conformity strengthens the relationship between campaign exposure and quit-smoking decisions.